Nonlinear thermal radiation and chemical reaction effects on Maxwell fluid flow with convectively heated plate in a porous medium. Issue 2 (3rd December 2018) - Hosseinzadeh, Kh.; Gholinia, M.; Jafari, B.; Ghanbarpour, A.; Olfian, H.; Ganji, D. D.
Abstract: This paper investigated the chemically reactive radiating flow by using a two‐dimensional Darcy‐Forchheimer model with the convectively heated plate. The nonlinear thermal radiation is described by Joule heating and heat generation. Also, Darcy‐Forchheimer equation is related to porous medium flows. For the solution of equations, we used the numerical method. Further, more physical interpretation of the parameters was demonstrated with figures. It is found that an increase in the Prandtl number had a direct effect on the Nusselt number and temperature, whereas the opposite scenario was observed in the Eckert number.